Formation of SnS2/Ni2S3 heterojunction on three-dimensional nickelframework for treating chromium(VI)-containing wastewater. (16th November 2017) - Yu, Chuang; Mao, Dong; Xia, Fei; Huang, Xiong; Li, Jiaqi; Liu, Wenyu; Fang, Dong
Abstract: Heterojunction system, as a considerable method, has been proved a good solution to improve photocatalysis. Herein, a novel SnS2 /Ni3 S2 heterojunction deposited on Ni foam (NF) (SnS2 /Ni3 S2 @NF) has been successfully synthesized by hydrothermal method. The photocatalytic activity has been improved due to the special heterostructure. Scanning electron microscopy, x-ray diffraction, Raman, UV–vis diffuse reflectance spectroscopy and photocatalytic test were employed to prove it. The SEM pictures showed that the surface of NF deposited a certain amount of SnS2 /Ni3 S2. And SnS2 /Ni3 S2 @NF heterojunction photocatalyst exhibits an excellent catalytic ability in the visible light region. Compared to pristine SnS2, the as-prepared SnS2 /Ni3 S2 @NF heterojunction showed increased photocatalytic activity toward Cr(VI) photoreduction under visible light irradiation. This work will be useful for the design of other photocatalyst for application in Cr(VI) removal.